Medea - Euripides (Greek tragedy in new translations., 2006)
"Euripides was one of the most popular and controversial of all the Greek tragedians, and his plays are marked by an independence of thought, ingenious dramatic devices, and a subtle variety of register and mood." "Medea is a story of betrayal and vengeance, and one which gives an excellent example of the prominence and complexity that Euripides gave to his female characters. Medea, wife of Jason, is incensed that her husband would leave her to make a political marriage after the many sacrifices she has made for him. In her wrath, she murders both his new bride and their own children, thus taking her revenge. This new translation does full justice to the lyricism of Euripides' original work, while a new introduction provides a guide to the play, complete with interesting details about the traditions and social issues that influenced Euripides' world."--Jacket